Psychosocial family factors and glycemic control among children aged 1-15 years with type 1 diabetes: a population-based survey - Haugstvedt Anne; Wentzel-Larsen Tore; Rokne Berit; Graue Marit (BMC, 2011)
Abstract Background Being the parents of children with diabetes is demanding. Jay Belsky's determinants of parenting model emphasizes both the personal psychological resources, the characteristics of the child and contextual sources such as parents' work, marital relations and social network support as important determinants for parenting. To better understand the factors influencing parental functioning among parents of children with type 1 diabetes, we aimed to investigate associations between the children's glycated hemoglobin (HbA1c) and 1) variables related to the parents' psychological and contextual resources, and 2) frequency of blood glucose measurement as a marker for diabetes-related parenting behavior. Methods Mothers (n = 103) and fathers (n = 97) of 115 children younger than 16 years old participated in a population-based survey. The questionnaire comprised the Life Orientation Test, the Oslo 3-item Social Support Scale, a single question regarding perceived social limitation because of the child's diabetes, the Relationship Satisfaction Scale and demographic and clinical variables. We investigated associations by using regression analysis. Related to the second aim hypoglycemic events, child age, diabetes duration, insulin regimen and comorbid diseases were included as covariates. Results The mean HbA1c was 8.1%, and 29% had HbA1c ≤ 7.5%. In multiple regression analysis, lower HbA1c was associated with higher education and stronger perceptions of social limitation among the mothers. A higher frequency of blood glucose measurement was significantly associated with lower HbA1c in bivariate analysis. Higher child age was significantly associated with higher HbA1c both in bivariate and multivariate analysis. A scatterplot indicated this association to be linear. Conclusions Most families do not reach recommended treatment goals for their child with type 1 diabetes. Concerning contextual sources of stress and support, the families who successfully reached the treatment goals had mothers with higher education and experienced a higher degree of social limitations because of the child's diabetes. The continuous increasing HbA1c by age, also during the years before puberty, may indicate a need for further exploring the associations between child characteristics, context-related variables and parenting behavior such as factors facilitating the transfer of parents' responsibility and motivation for continued frequent treatment tasks to their growing children.